Hidden Rhythm in Residential Units with the Everyday Human Activity Residential Units in Aadhamiyah as A Case Study - Azzam Mahmood, Nada; Mohammed Hussain, Asmaa (International Journal of Engineering and Technology, 2018)
Meaning of home has been changed through time in relating human connection to his environment. We can notice the gap from the traditional models of housing to the modern models regarding the concept of house. The research aims and trying to explore the nature of this relationship and the transformations took place in changing the meaning of home. As a result, the main research problem has been identified as "lack of knowledge regarding the relationship between daily life rhythm and residential spaces today and the effect of physical space on human rhythm and its relation with the environment ". The research goals aim to identify residential spaces raises according to daily life experience and daily rhythm to get environments that sustain space feeling and continuity of residential units with the humanity of today, the research hypotheses addressed as:Hidden rhythm of daily life reinforces human being with his environment through sustaining interactive spaces.Â The research suspected two types of rhythms: the first is Isorythmic Eurhmia rhythms that sustain interactive spaces; the second is Arrhythmia rhythms that lead to repellant unlivable spaces. The research finds traditional modes of sheltering corresponded with natureâ€™s rhythms at the same time, evoked rich patterns of social rhythms with healthy interactive spaces reaching to Isorythmic Eurhmia rhythms by Â harmonious synchronization of different rhythms interact with the environment, dilvers locality, identity and social interaction. While modern houses fail to accommodate changing needs producing arrhythmia rhythms with isolation and disinterest behaviors contradicting with nature's rhythm, have spatial control that achieves universality and restrict relationship between time space and human activities inside the space.Â